2-Mercaptobenzimidazole, 2-Mercaptobenzothiazole, and Thioglycolic Acid in an Electroless Nickel-Plating Bath - Ahmet Ozan Gezerman; Burcu Didem Çorbacıoğlu (Journal of Chemistry, 2015)
The use of three different materials, 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, and thioglycolic acid, was investigated to improve the performance of electroless nickel-plating baths. By changing the concentrations of these materials, sample plates were coated. Optical microscope images were obtained by selecting representative coated plates. From the results of the investigations, the effects of these materials on electroless nickel plating were observed, and the most appropriate amounts of these materials for nickel plating were determined. Moreover, the nickel plating speed observed with the bath solution containing 2-mercaptobenzimidazole, 2-mercaptobenzothiazole, and thioglycolic acid is higher than that in the case of traditional electroless plating baths, but the nickel consumption amount in the former case is lower. In order to minimize the waste water generated from electroless nickel-plating baths, we determined the lowest amounts of the chemicals that can be used for the concentrations reported in the literature.